2018
DOI: 10.1097/jom.0000000000001284
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Declines in Kidney Function in Sugarcane Workers in Guatemala

Abstract: Objectives:To characterize kidney function of sugarcane workers in Guatemala over the 6-month harvest and identify risk factors associated with changes in kidney function.Methods:Demographic and biological data were collected for 330 sugarcane cutters at the beginning and end of the harvest. Multivariable regression analyses were used to assess factors related to kidney function.Results:A decline in kidney function across the harvest was observed in 36% of the participants. Risk factors associated with this de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
62
1
7

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 50 publications
(76 citation statements)
references
References 34 publications
1
62
1
7
Order By: Relevance
“…All four of these exposures were nearly ubiquitous (present in .80% of patients with tubulointerstitial kidney disease), and they point us in the direction of environment and lifestyle rather than genetics alone (because although a positive family history was more prevalent in patients with tubulointerstitial kidney disease, it was reported in only about one third of patients). The same correlates, with the exception of well water use, were observed in a recent study evaluating risk factors for postharvest eGFR decline in Guatemala (30). In contrast to patients with Mesoamerican nephropathy who seem to have clearly defined tasks on the sugarcane farm and may experience differential task-dependent risks for kidney disease (31,32), patients with tubulointerstitial kidney disease in Sri Lanka were essentially running the whole farm.…”
Section: Discussionsupporting
confidence: 65%
“…All four of these exposures were nearly ubiquitous (present in .80% of patients with tubulointerstitial kidney disease), and they point us in the direction of environment and lifestyle rather than genetics alone (because although a positive family history was more prevalent in patients with tubulointerstitial kidney disease, it was reported in only about one third of patients). The same correlates, with the exception of well water use, were observed in a recent study evaluating risk factors for postharvest eGFR decline in Guatemala (30). In contrast to patients with Mesoamerican nephropathy who seem to have clearly defined tasks on the sugarcane farm and may experience differential task-dependent risks for kidney disease (31,32), patients with tubulointerstitial kidney disease in Sri Lanka were essentially running the whole farm.…”
Section: Discussionsupporting
confidence: 65%
“…In this study, cross-shift changes at the start of the harvest predicted the longitudinal kidney function decline (47). In Guatemala, 6% of young male cutters and other field workers had a cross-harvest eGFR decline >20% of baseline (53). In a retrospective cohort analysis, 19% of cane cutters, who have the highest physical workload, developed kidney injury at end of harvest, compared to less than 6% of other field workers, and no kidney injury among pesticide applicators or irrigation workers (54).…”
Section: Analytical Epidemiologic Studies Highlight Occupational Heatmentioning
confidence: 76%
“…Several of the above-mentioned cross-shift and cross-harvest studies on heat stress simultaneously addressed pesticide exposures. Except for an isolated association between low pre-shift eGFR and self-reported use of carbamate insecticides in El Salvador (46,63), none of these studies found associations with pesticide use; interactions were not examined (48,51,53,55,58,63). However, the relative difficulty of measuring environmental exposures to toxicants (such as pesticides) or heat stress could obscure their potential role, when compared to potential genetic determinants which typically have less measurement error (67).…”
Section: Pesticides and Metalsmentioning
confidence: 99%
“…Each year, prior to the start of the 6-month sugarcane harvest, the agribusiness conducts a pre-employment screening which includes a medical exam (blood pressure, heart rate, height, and weight), questionnaire (demographic, lifestyle, medical, and occupational history questions), and venipuncture for measurement of serum creatinine of each individual seeking employment as a sugarcane harvester. Full details on recruitment and preemployment screening are published elsewhere [20]. Subjects for our analysis were retrospectively selected from workers seeking employment as sugarcane harvesters between November 2012 and November 2015 at the agribusiness.…”
Section: Cohortmentioning
confidence: 99%
“…Because these data were collected for hiring purposes, we were limited in our ability to examine additional hypothesized risk factors such as heat exposure [6,11], use of pesticides [36,37], and exposure to heavy metals [34,38]. Due to the structure of our data, we were unable to assess the differences in recurrent dehydration [11], NSAID use [20], and other factors previously implicated in the development of the disease between the two identified groups. There is a possibility of nondifferential misclassification of survey variables including smoking status and alcohol intake.…”
Section: Limitationsmentioning
confidence: 99%